An Inherent Strain Method Using Progressive Element Activation for Fast Distortion Calculation in Directed Energy Deposition - Georg Seitz; Patrick Bantle; Max Biegler; Beatrix A. M. Elsner; Michael Rethmeier (Metals)
The finite element analysis (FEA) simulation of directed energy deposition (DED) processes offers many potential cost savings during the build job optimization process, through, e.g., distortion predictions. However, the biggest challenge is the long calculation time, frequently exceeding the actual build time. One way of simplifying the simulation with the aim of reducing the calculation times is the inherent strain method. While this method is already used commercially in the simulation of powder bed-based processes and conventional welding technologies, its use in DED is still the subject of research. In this work, an inverse determination of an inherent strain is carried out on a 20-layer-high, single-track-wide wall, common theories are reviewed, and an approach based on thermal strain is introduced. As a result, the calculation time could be reduced by 83% and the accuracy remained at 92%.